Pelatihan Penggunaan Perangkat Pembelajaran Huruf Braille untuk Siswa Tuna Netra - Purnama, Sevia Indah; Afandi, Mas Aly; Hikmah, Irmayatul; Arifani, Erlina Nur; Puteri, Keyza Nuralifa; Elsalami, Puspa Maudi; Setiawan, Andri Juli (Madani : Indonesian Journal of Civil Society, 2025)
Visually impaired children have limitations in learning Braille due to limited resources and improper facilities. These limitations mean that independent learning activities at home cannot be carried out because they require a teacher who understands Braille. This service activity is carried out to provide training to blind children on the use of Braille learning tools. This service aims to enable blind children to learn Braille letters independently without needing a teacher. Training activities consist of an introduction to Braille letters, an explanation of Braille learning devices, and training on the use of devices for self-learning. The results of the service show that Braille learning technology devices help students in learning independently. There are 6 students and 1 blind teacher who became respondents who agreed that the learning device can be used independently without the help of a companion teacher. Respondents also agreed that the use of assistive technology in learning devices is easy to use. Students have been able to use learning tools independently without the help of a companion teacher to study outside of school.